2015
DOI: 10.5507/bp.2015.044
|View full text |Cite
|
Sign up to set email alerts
|

Refractory cardiogenic shock due to extensive anterior STEMI with covered left ventricular free wall rupture treated with awake VA-ECMO and LVAD as a double bridge to heart transplantation - collaboration of three cardiac centres

Abstract: Aim.To highlight an optimal collaborative strategy of three different levels of specialized care cardiac centres. Background. Refractory cardiogenic shock is a life-threatening condition. A myocardial recovery is not achieved in many cases despite all efforts and subsequently the heart transplantation remains an ultimate option. Thereby, the use of extracorporeal membrane oxygenation (ECMO) followed by a ventricular assist device in staged bridging provides an attractive approach. Case report. We report on an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“… 10 Likewise, the strategy has been attempted in patients undergoing high-risk percutaneous coronary intervention or suffering from refractory cardiogenic shock, but no studies involving a population bridged to transplantation were found. 28 29 30 Therefore, we investigated whether the use of an early extubation ECMO strategy is beneficial in patients who received VA-ECMO as a bridge to HT and found that early extubation VA-ECMO was associated with reductions in the rates of delirium and infection. A subgroup analysis with successfully transplanted patients also showed the existence of less postoperative days on mechanical ventilation and reduced ICU stay length in the early extubation group, presumably leading to reductions in medical costs and complications related to prolonged hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“… 10 Likewise, the strategy has been attempted in patients undergoing high-risk percutaneous coronary intervention or suffering from refractory cardiogenic shock, but no studies involving a population bridged to transplantation were found. 28 29 30 Therefore, we investigated whether the use of an early extubation ECMO strategy is beneficial in patients who received VA-ECMO as a bridge to HT and found that early extubation VA-ECMO was associated with reductions in the rates of delirium and infection. A subgroup analysis with successfully transplanted patients also showed the existence of less postoperative days on mechanical ventilation and reduced ICU stay length in the early extubation group, presumably leading to reductions in medical costs and complications related to prolonged hospitalization.…”
Section: Discussionmentioning
confidence: 99%
“…The literature on LVAD implantation after contained free wall rupture is limited to few case reports. 1 6 7 Two reasons precluded implantation of an extracorporeal LVAD with a left atrial inflow cannula in our patient: the contained rupture with a potential for late bleeding and a good quality of life postoperatively.…”
Section: Discussionmentioning
confidence: 98%
“…Implantation after contained rupture of the free wall of the left ventricle (pseudoaneurysm) is challenging and information scarce. 1 …”
Section: Introductionmentioning
confidence: 99%
“…Commonly, intra-aortic counterpulsation is used to reduce left ventricular afterload and left-to-right shunting in ischemic VSD to stabilize patients for surgical repair. There are a few cases reported in which patients with CS after MI received veno-arterial extracorporeal membrane oxygenation (vaEC-MO) as bridging prior to surgery with good results (6)(7)(8)(9). Recently, vaECMO has been increasingly used in order to improve hemodynamic instable patients (10).…”
Section: Introductionmentioning
confidence: 99%